PENGARUH BUDAYA PERUSAHAAN DAN KOMITMEN KERJA TERHADAP KINERJA KARYAWAN PT. FUMIRA SEMARANG - Paramesthi, Rica Anindita; Prihatini, Apriatni Endang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2017)
Corporate culture and employee commitment are important factors for the achievement of employee performance. PT. FUMIRA semarang is a company engaged in the field of manufacture and strives to provide the best service for customers, and therefore requires human resources with good performance. This type of research is explanatory research, that explain the relation between one variable with other variable. Amount of sample is 55 respondents, they are the employees of PT. FUMIRA Semarang. Sample technique used proportional random sampling. Data collection used questionnaire with likert measurement scale. Data analysis method used validity and reability test, correlation coefficient (R), simple linear regression, multiple linear regression, coefficicient of determination (R2), F test, and t test used SPSS program version 22.0.Suggestions can be submitted is PT. FUMIRA semarang needs to be able to maintain employee commitments and improve employees' understanding of the company’s culture.